A prospective comparative analysis of functional outcomes and recurrence rates in wrist ganglion cysts: excision versus aspiration versus threading - Barnwal, Sanjay; Sanghavi, Tejas; Shekade, Pramod; Ghag, Niranjan S. (International Journal of Research in Orthopaedics, 2026)
Background: Wrist ganglion cysts are recognized as the most common benign soft-tissue tumors of the hand and wrist. Despite multiple available treatment modalities, there is no consensus regarding the optimal approach, particularly in resource-limited settings. This study aims to evaluate and compare the functional outcomes, complication profiles, and recurrence rates of three common treatments: surgical excision, aspiration, and threading. Methods: This prospective observational comparative study included 91 patients with symptomatic wrist ganglion cysts treated at a rural tertiary care teaching hospital. Based on patient preference and feasibility, participants were categorized into three intervention groups: surgical excision (n=37), aspiration (n=26), and the threading/transfixation technique (n=28). Outcomes were assessed using visual analog scale (VAS) pain scores, a 5-point patient satisfaction scale, recurrence rates, and operative parameters such as procedure time. Results: All treatment modalities achieved a significant reduction in postoperative pain, indicating comparable short-term symptomatic relief. However, long-term efficacy varied significantly; excision demonstrated the lowest recurrence rate at 5.4%, followed by threading at 14.3%, while aspiration showed a highly significant recurrence rate of 65.4%. Patient satisfaction was highest following excision (mean 4.86) and threading (4.68), and comparatively lower for aspiration (4.11). While excision required a longer procedural time (11.2 minutes), threading and aspiration were minimally invasive and faster (4.7 and 4.8 minutes, respectively). Conclusions: Surgical excision provides the highest patient satisfaction and lowest recurrence rate, reaffirming it as the definitive gold standard for treating wrist ganglion cysts. However, the threading technique emerges as a highly practical, minimally invasive alternative that successfully balances low recurrence with feasibility, making it especially valuable in resource-constrained environments. Aspiration, due to its significantly higher recurrence rates, is limited in its role as a definitive long-term treatment.